The changing facets of public administration in the United Arab Emirates - Sarker, Abu Elias; Attmay, Alaa Aldin Abdul Rahim A Al (2018)
This article is an in-depth profile of the public administration system in the United Arab Emirates (UAE). It specifically focuses on the relationship between the state, the market and civil society, the structure of the government and the civil service system and its functional areas. Reform initiatives undertaken in all these areas over the last decade have also been discussed. The findings reveal that the public administration system in the UAE has demonstrated considerable developments in facilitating the market forces, opening space for civil society and modernizing the civil service system. - Reproduced.
Keywords: Administrative reforms - United Arab Emirates; Civil service - United Arab Emirates